Flaubert en Allemagne : un parcours avec Kurt Drawert - Florence Vatan (Flaubert: Revue Critique et Génétique)
This article examines the reading that Kurt Drawert, a writer who grew up in the former GDR, offers of Flaubert, and especially of Madame Bovary, in Emma. Ein Weg (2005). Drawert weaves numerous aesthetic and biographical connections with Flaubert. An exemplary writer in terms of his demanding aesthetic, Flaubert also offers, in Drawert’s eyes, an early critique of the failings of the capitalist world and of the violence of scientistic reason.